The impact of emulsion droplet size on in vitro lipolysis rate and in vivo plasma uptake kinetics of triglycerides and vitamin D3 in rats. Issue 7 (22nd March 2021) - Dille, Morten J.; Baydin, Tuna; Kristiansen, Kåre A.; Draget, Kurt I.
Abstract : Emulsions with smaller droplets are more rapidly lipolyzed in the intestine, resulting in increased uptake to plasma of triglycerides. However, the uptake of vitamin D3 from the same emulsions is not significantly affected by droplet size. Abstract : Emulsions play an important role in the process of triglyceride (TG) digestion (lipolysis). Through emulsification, the oil–water interface is increased by orders of magnitude. This often leads to faster and more efficient lipolysis, which is potentially beneficial for the intestinal uptake of oils and lipophilic compounds. In this paper, we first examined the effect of emulsion droplet size on the in vitro lipolysis rate. Then an in vivo experiment was performed, to examine the plasma uptake kinetics of TGs and vitamin D3 (vitD3 ) over a 24 hours period after oral administration of the emulsions in rats. Basic corn oil emulsions loaded with vitD3 were prepared using polysorbate 80 as the emulsifier, with three different droplet sizes (D[3, 2]): ∼3 μm (large), ∼1 μm (medium) and ∼0.3 μm (small). In vitro lipolysis experiments showed, as expected, that smaller droplets were lipolyzed more rapidly. However, the medium emulsion had by far the highest rate of lipolysis per surface area. This was attributed to bile salt limitation, polysorbate 80 lipolysis inhibition and TG digestion product accumulation. In vivo, the two smallest emulsions showed the highest uptake ( C max and AUC) of vitD3 and TG, while the largest emulsion and bulk oil control showed lower values. However, only the (incremental) TG plasma values and kinetics displayed some statistically significant differences. These findings may have relevance for the formulation of functional foods/beverages or delivery units containing oils or lipophilic bioactives.